Die besetzte Anstalt: die Psychiatrie in Kocborowo/Konradstein (Polen/Westpreußen) und ihre Opfer im Zweiten Weltkrieg = Szpital psychiatryczny pod okupacją : psychiatra w Kocborowie/Konradstein (Polska/Prusy Zachodnie) i jef ofiary w czasie Drugiej Wojny Światowej - Parzer, Robert; Rotzoll, Maike; Schulze, Dietmar (Forschung für die Praxis - Hochschulschriften, 2019)
A brief history of a psychiatric hospital in Kocborowo, Poland (or Konradstein, West Prussia) during the Nazi occupation. Includes biographical sketches of 16 patients, some of whom were among the 1,692 murdered by members of an SS-Kommando unit in the area